GEOMORPHOLOGICAL DEVELOPMENT OF THE MURIA PALAEOSTRAIT IN RELATION TO THE MORPHODYNAMICS OF THE WULAN DELTA, CENTRAL JAVA - Sunarto Sunarto (Faculty of Geography, Universitas Gadjah Mada, 2008)
The research area is situated in the Demak, Jepara, Pati and Kudusregencies of the CentralJava Province. The objectives of the research are: (1) theinvestigation of the geomorphologic development of the Muria Palaeo-Strait inCentral Java and (2) the analysis of the morphodynamicsof the WulanDelta. Amorphographic- morphogeneticapproach was used to interpret the genesJsandsubsequent evolution of the coastal lowlands in the surroundings of the MuriaVolcano. The data analysis techniques, based on cause-effect assessment andanalogy, were implemented in four steps, such as: (a) descriptive, (b) comparative,.(c) associative and (d) causative stages. The results of the research can besummarized as follows: The coastal plain situated to the south of the MuriaVolcano was originally a shallow strait and subsequently became a mangrovecoveredtidal flat with many creeks. Ultimately this tidal flat evolved into analluvial/coastal plain with natural levees and back swamps. The coastal area in thewest was still inundated by the sea around 6,000 yrs BP. This is evidenced by the14C-dating 6,530 + 120 yrs BP of a coral reef situated at 25 cms a.s.l. The presentbeach ridge has an age 4,600 + 100 yrs BP and originated as a barrier bar. Thecoastal area in the east is characterized by the occurrence of four sequential beachridge complexes at elevations of 580, 520, 220 and 125 cms respectively. Theyhave been 14C-dated 5,860 + 110 yrs BP, 5,090 + 100 yrs BP, 3,530 + 100 yrs BPand 1,760 + 120 yrs BP. Since 1,760 yrs BP nofurther beach ridges wereformed,a tidal flat developed instead. The shape of the Wulan Delta changed from actuateto digit ate in the period of 1925 - 1995, mainly due to human interference with theriver for purposes of irrigation. The growth of the Wulan Delta affected the hydrodynamical situation offshore of Jepara. These hydrodynamic changes resulted inmarine erosion in the rural areas in the Jepara Regency and chewier formation inthe rural areas of the Demak Regency.